Iliopsoas myositis ossificans after transverse myelitis in a child: a case report - Yin, Haoran; Li, Jie; Su, Yongtao (Frontiers in Surgery, 2025)
IntroductionAcute transverse myelitis in children is a rapidly progressive disease of unknown etiology, with some patients experiencing lifelong paralysis. Myositis ossificans (MO) refers to heterotopic ossification within soft tissues. Neurogenic MO is rare in clinical practice and is often misdiagnosed, particularly in pediatric patients who are unable to clearly describe their symptoms. Diagnosis typically relies on imaging studies.MethodsThis report describes a case of an 8-year-old child who developed paraplegia following a diagnosis of acute transverse myelitis and subsequently presented with MO of the iliopsoas muscle, likely resulting from the spinal cord injury in combination with a distal femoral fracture, although the ossification itself developed in the iliopsoas region rather than at the fracture site.ResultsThe patient exhibited progressive limitation of hip joint movement during rehabilitation. X-ray imaging revealed high-density ossification in the iliopsoas region. After six months, the ossification had matured extensively, and surgical resection was performed. The patient's hip mobility improved postoperatively. During a 3-year follow-up period, there was no recurrence of ossification.DiscussionThis case highlights the potential development of neurogenic MO in pediatric patients with spinal cord injury, even when the ossification does not occur at the fracture site. We discuss the challenges in diagnosing and treating such conditions in children and review current diagnostic and therapeutic advancements. This case contributes to the understanding of neurogenic MO in pediatric patients and provides insights for managing similar conditions.